High evening cortisol level is associated with low TBS and increased prevalent vertebral fractures: OsteoLaus study - Gonzalez Rodriguez, Elena; Kühner, Christine (The journal of clinical endocrinology & metabolism, 2017)
Context: Increased evening cortisol levels have been implicated in bone mineral density (BMD) loss. The effect on bone microarchitecture and fracture risk has never been studied. Objective: To study the relationship between salivary cortisol circadian rhythm and (1) trabecular bone score (TBS) and (2) fracture prevalence. Design, Setting, Patients, and Interventions: Cross-sectional study including 608 women >50 years old (mean = 65.5) from the OsteoLaus cohort. Data included the FRAX© questionnaire, BMD, TBS and vertebral fracture (VFx) assessment by dual X-ray absorptiometry, and measures of salivary cortisol (awakening, 30 minutes thereafter, 11 am, and 8 pm). Results: In the multivariate model, participants in the highest tertile of 8 pm salivary cortisol (sc-8 pm) (mean = 5.7 ± 2.5 nmol/L) vs lowest tertile (1.7 ± 0.4 nmol/L) had lower TBS values (1.27 vs 1.29; P = 0.02), more prevalent VFx grades 2 and 3 (odds ratio = 5.34; P = 0.012), low-trauma fractures (odds ratio = 1.80; P = 0.036), and major osteoporotic fractures (odds ratio = 1.96; P = 0.042), without difference in lumbar spine BMD (0.91 vs 0.92 g/cm2; P = 0.431). VFx prevalence was associated with sc-8 pm and TBS independently of each other and of other risk factors. The cut-point for sc-8 pm correlating with the presence of >1 VFx was 3.62 nmol/L (sensitivity 0.74, specificity 0.66). Conclusions: High sc-8 pm is associated with low TBS and an increased prevalence of radiologic VFx independently of other risk factors. Measurement of sc-8 pm may add relevant information in the assessment of fracture risk.